MORPHOLOGICAL FEATURES OF THE REGIONAL BLOODSTREAM OF SKIN WHEN CARRYING OUT AESTHETIC OPERATIONS IN THE FACE LATERAL AREA - Куцевляк, В.І.; Білаш, С.М. (World of Medicine and Biology, 2016)
The face of each individual is the main characteristic of appearance, differs in the identity, therefore it is clear to keep the desire to preserve the features during life. At profound age changes by the most effective there is a surgical method of treatment. The morphometric assessment and radiological researches of features of blood supply of surface tissues of the face lateral sides were carried out on 30 preparations of skin and fatty grafts. The analysis of results of morphometric research indicates that in a term and a gipoderma of parotidand chewing are arteria land venous vessels in comparison with buccal area are less expressed. Features the angioarkhitektonik of skin and a gipoderma of a side face zone who are expressed available two main sources of blood supply (a branch of a facial and cross artery of the person) are defined by radiological and morphometric researches.